More than ten million years of hyper-aridity recorded in the Atacama Gravels. (15th April 2018) - Sun, Tao; Bao, Huiming; Reich, Martin; Hemming, Sidney R.
Abstract: The Atacama Desert's hyper-aridity is closely linked to the development of world-class copper and nitrate/iodine ores and to regional tectonics and global paleoclimate changes in the Cenozoic era. The timing when the hyper-aridity commenced remains controversial, with proposed ages ranging from Late Oligocene to Pleistocene. In this study, we provide an independent constraint on the initiation of Atacama hyper-aridity utilizing a 100-m deep profile within the Atacama Gravels and underneath porphyry copper deposit in Spence, northern Chile. The overall high concentration of sulfate (up to 10 wt%) and a multimodal distribution of water soluble salt (sulfates, chlorides and nitrates) indicate multiple generations of sedimentation and salt accumulation events under semi-arid to hyper-arid climate conditions. The multiple sulfate isotope compositions (Δ 17 O, δ 18 O, δ 34 S) of the upper section (−15.0 to −34.5 m) are close to those of modern hyperarid surface sulfates, while the lower section (−34.5 to −65 m) displays a depth dependent isotope trend that is best interpreted as marking a period of climate change from semi-arid to hyper-arid. When these data are combined with new chronological 40 Ar/ 39 Ar dates obtained from a volcanic ash layer at depth of −28.0 m, our results show that hyper-arid condition in the Atacama Desert was prevailing at least prior to 9.47 Ma and may go back as old as the middle Miocene.